Analysis of Learning Difficulties of Class XII High School Students on Genetic Material - Desi Eka Nur Fitriana; Dini Khanifa Yanti; Annisa Khotimah Yunus; Randy Eka Aprilya (International Journal of Biology Education Towards Sustainable Development, 2022)
Learning difficulties are obstacles or distractions experienced by students in learning activities that hinder the achievement of learning objectives. In this case, students have learning difficulties with genetic material. Genetics is the science that studies the inheritance of traits, similarities, and differences in traits inherited by living things or passed on from parents to their offspring. This material is one of the materials studied in Biology in class XII. This study aimed to analyze the learning difficulties of class XII students on genetics. This descriptive study aims to describe and determine the causes of learning difficulties on genetics for class XII students at one high school in Cibeber, Indonesia. The data collection technique in this study used a questionnaire with a sample of class XII students at a high school in Banten, Indonesia. Through the research that has been done, it can be concluded that students have student learning difficulties found in genetic material (chromosomes, genes, DNA, and RNA) and foreign concepts and terms found in the process of cell division and inheritance.